The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.14419/ijans.v5i1.5565
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: its psychological effects on family caregivers

Abstract: Purpose: Caregivers of patients diagnosed with schizophrenia experience moderate to severe caregiver burden and are at risk for developing mental disorders. This study explores the psychological effects and coping strategies of family caregivers of relatives diagnosed with schizophrenia in the developing world. Methods: This qualitative study used the register of a community mental health clinic at a Jamaican hospital to purposively select and recruit five primary family caregivers of clients diagnosed with sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…15,[20][21][22][23][24] At this point, stress and coping situations gain importance. 20,25,26 In a study conducted by Riley-McHugh et al, which investigated stress-coping mechanisms and psychosocial effects of caregiving on caregivers, the stress levels of the caregivers increased when they had insufficient coping resources, social support, and communication skills. 26 These symptoms may aggravate the economic and social burden of caregivers.…”
Section: Whilementioning
confidence: 99%
See 2 more Smart Citations
“…15,[20][21][22][23][24] At this point, stress and coping situations gain importance. 20,25,26 In a study conducted by Riley-McHugh et al, which investigated stress-coping mechanisms and psychosocial effects of caregiving on caregivers, the stress levels of the caregivers increased when they had insufficient coping resources, social support, and communication skills. 26 These symptoms may aggravate the economic and social burden of caregivers.…”
Section: Whilementioning
confidence: 99%
“…20,25,26 In a study conducted by Riley-McHugh et al, which investigated stress-coping mechanisms and psychosocial effects of caregiving on caregivers, the stress levels of the caregivers increased when they had insufficient coping resources, social support, and communication skills. 26 These symptoms may aggravate the economic and social burden of caregivers. Studies have shown that the symptoms of depression and stress are accompanied by stigma and a maintenance burden.…”
Section: Whilementioning
confidence: 99%
See 1 more Smart Citation
“…Family members are generally responsible for the care of schizophrenic patients all over the world (Kertchok, 2014; Stengard, 2003). Especially, the studies in developing countries show that caregiving is the work of the extended family (Riley-McHugh, Brown, Lindo, 2016; Talwar & Matheiken, 2010; Yusuf, Nuhu, & Akinbiyi, 2009). Moreover, family’s importance increased with the community-based approach (Chan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have identified the difficulties faced by the close persons of people with a SMI (Chien, 2010;Matens and Addington, 2001;Riley-McHugh et al, 2016). R9 had been stealing money from his parents and abusing drugs; after the end of the intensive part of the psychotherapeutic programme he was able to speak about his wish to repay the money and to find a temporary job, thus showing a strong trust towards the group.…”
Section: Psychotherapeutic Programme In the Context Of Participants' mentioning
confidence: 99%